Performance assessment for life extending control of steam turbine based on polynomial method. (5th September 2016) - Sun, Yong-Jian; Wang, Ya-Ling; Li, Meng; Wei, Jun
Highlights: Establish the low cycle fatigue damage model of steam turbine rotor. A performance assessment benchmark feasible in engineering is proposed. A polynomial based assessment method for control performance is developed. Decompose nonlinear LCF damage model to static nonlinear part and dynamic linear part. Abstract: Damage modeling and life extending control for steam turbine are studied in this work. Taking the rolling process of a 300 MW steam turbine unit as an example, this paper proposes a control performance benchmark for life extending controller. And a polynomial control performance assessment method is developed. Nonlinear low cycle fatigue damage model is decomposed to static nonlinear part and dynamic linear part. This mathematical model represents a class of damage assessment problems. A numerical simulation using practical industrial data validates the contribution of present work.